Pengaruh Intensitas Mengakses Video Pembelajaran IPS di Youtube Terhadap Minat Baca Buku IPS - Ningtias, Widya Asmi; Sujarwo, Sujarwo (Program Studi Pendidikan IPS Universitas Negeri Jakarta, 2021)
This study aims to determine whether the intensity of the use of social studies learning videos on YouTube has an effect on interest in reading social studies books for class IX students at SMPN 20 Jakarta. This type of research is quantitative with a survey method through a questionnaire and using a Likert scale. The sample in the study amounted to 81 students using the non-probability sampling method with purposive sampling technique as the sample determination. Hypothesis testing was carried out with the help of SPSS Statistic 26. Based on the testing of data analysis requirements and hypothesis testing that had been carried out, the T test value was 12.451> 1.99, meaning that H1 was accepted which